2021
DOI: 10.1111/ijcp.14630
|View full text |Cite
|
Sign up to set email alerts
|

The association between psoriasis and psoriatic arthritis with the risk of osteoporosis, osteopenia and bone fractures: A systematic review and meta‐analysis

Abstract: Psoriasis is a chronic inflammatory disease, which primarily engages the skin and affects approximately 2-4% of the general population; the pathogenesis of psoriasis involves interplay between environmental and genetic risk factors. 1,2 About 6% to 42% of people with psoriasis develop an inflammatory form of osteoarthritis called psoriatic arthritis (PsA). 3 This condition causes the joints to become swollen, painful and tender to the touch, but, disorders of the peripheral joint inflammation, axial skeleton, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…Further, patients with Ps did not have a higher risk of OP than the controls; but, interestingly, did have an increased OR of sustaining fractures unrelated to lower BMD/OP. Similar findings were reported by Sepehri et al., 31 demonstrating an increased risk of fracture but not OP/OPe in psoriatic disease. Chandran et al., 32 showed a possible association between various factors and low BMD in PsA, but with inconsistent findings.…”
Section: Discussionsupporting
confidence: 90%
“…Further, patients with Ps did not have a higher risk of OP than the controls; but, interestingly, did have an increased OR of sustaining fractures unrelated to lower BMD/OP. Similar findings were reported by Sepehri et al., 31 demonstrating an increased risk of fracture but not OP/OPe in psoriatic disease. Chandran et al., 32 showed a possible association between various factors and low BMD in PsA, but with inconsistent findings.…”
Section: Discussionsupporting
confidence: 90%
“…Studies have yielded inconclusive results on the association between psoriatic/PsA and bone loss (180)(181)(182), a systematic review and meta-analysis including 12 studies concluded that patients with psoriasis/PsA have an increased risk of fractures (psoriasis: OR = 1.29, 95%CI = 1.02-1.63; PsA: OR = 2.88, 95%CI = 1.51-5.48). However there is little evidence supporting the association between psoriasis and osteoporosis/osteopenia (osteoporosis, psoriasis: OR, 1.28, 95%CI 0.86-1.90; PsA: OR, 1.32, 95%CI: 0.79-2.19; osteopenia, psoriasis: OR, 1.50, 95%CI: 0.75-3.02; PsA: OR, 1.61, 95%CI: 0.67-3.85) (183). Psoriasis increased the risk of osteoporosis in patients aged ≥ 40 years in Korea (182).…”
Section: Osteoporosis and Fracturementioning
confidence: 99%
“…We observed that psoriasis also evaluated the risk of CKD ( 46 ), end-stage CKD ( 46 ), uveitis ( 47 ), fracture ( 48 ), geographic tongue ( 49 ), multiple sclerosis ( 50 ), erectile dysfunction ( 51 ), aortic aneurysm ( 52 ), schizophrenia ( 53 ), prevalence and incidence of depression ( 54 ), and prevalence of anxiety ( 54 ). However, meta-analyses also reported the lack of significant correlation between psoriasis and osteoporosis ( 55 ), osteopenia ( 55 ), suicide ( 56 ), suicide attempt ( 56 ), and venous thromboembolism (VTE) ( 57 ) ( Figure 8 ).…”
Section: Resultsmentioning
confidence: 99%